Association between serum uric acid, hyperuricemia and periodontitis: a cross-sectional study using NHANES data - Jing Xu; Yifan Jia; Zhi Mao; Xiaoxi Wei; Tianyuan Qiu; Min Hu (BMC, 2023)
Abstract Objectives Diabetes and other metabolic diseases have been linked to the development of periodontitis, but little research has been done to determine whether serum uric acid (SUA) levels and hyperuricemia play a role. This study aimed to investigate the relationship between SUA, hyperuricemia, and periodontitis. Methods Using data from the National Health and Nutrition Examination Survey (NHANES) 2011-2014, we created a nationally representative data set. We used multivariable logistic regression models to assess the relationship between SUA, hyperuricemia, and periodontitis and presented odds ratios (OR) in women and men, respectively. Results In women, adjusted multivariable regression models showed that SUA (4.1-4.3mg/dl) was associated with higher odds of periodontitis (OR = 1.43; 95% confidence interval (CI):1.0 ~ 2.03, p = 0.047) with SUA (≤ 3.3mg/dl) as reference. The risk of periodontitis tended to increase slightly but insignificantly with increasing SUA levels, and the adverse effects occurred only when SUA increased to a certain level, and then reached a plateau. In men, the adjusted OR values for SUA (4.9-5.2mg/dl), SUA (5.3-5.5mg/dl), SUA (5.9-6.2mg/dl), and SUA (6.3-6.5mg/dl) were 0.66 (95% CI: 0.45 ~ 0.96, p = 0.029), 0.58 (95% CI: 0.40 ~ 0.85, p = 0.006), 0.67(95% CI: 0.47 ~ 0.97, p = 0.035), and 0.67 (95% CI: 0.45 ~ 0.99, p = 0.043), respectively, with SUA (≤ 4.3mg/dl) as reference. The elevated SUA levels are protective against periodontitis, but there is a range within which the risk of periodontitis decreases, followed by a non-significant tendency to increase. Conclusions The levels of SUA that are linked to the risk of periodontitis. Future prospective longitudinal studies and strategies are required to further confirm whether controlled SUA treatment is an effective adjunct to systematic periodontal therapy and whether SUA can be used as a diagnostic biomarker to assess the risk or progression of periodontitis.